Quantitative Characteristics and Comparative Analysis of Higher Education Development Trends in Latvia, Lithuania and Estonia - Nikita Valer’evich Nikiforovs (Сравнительная политика)
The article analyzes the trends of higher education in Latvia, Lithuania and Estonia in a comparative perspective taking into account such trends as the strengthening of statehood and membership in the EU and the Bologna process. The author identifies important trends in the higher education system of the three countries using fresh demographic data.